2003
DOI: 10.1046/j.1523-1755.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of calcium oxalate crystals by renal tubular cells: A nephron segment–specific process?

Abstract: Internalization of calcium oxalate crystals by renal tubular cells: A nephron segment-specific process? Background. Crystal retention in the kidney is caused by the interaction between crystals and the cells lining the renal tubules. These interactions involve crystal attachment, followed by internalization or not. Here, we studied the ability of various renal tubular cell lines to internalize calcium oxalate monohydrate (COM) crystals. Methods. Crystal-cell interactions are studied by light-, electron-, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…The treatment time of 6 hours in this study is consistent with that described in previous studies on kidney stones. 22,23 We selected the concentrations of H 2 O 2 and crystals based on the following reasons. The commonly used H 2 O 2 concentration to induce cell injury ranged from 10 to 1,000 μmol/L.…”
Section: Cell Culturementioning
confidence: 99%
“…The treatment time of 6 hours in this study is consistent with that described in previous studies on kidney stones. 22,23 We selected the concentrations of H 2 O 2 and crystals based on the following reasons. The commonly used H 2 O 2 concentration to induce cell injury ranged from 10 to 1,000 μmol/L.…”
Section: Cell Culturementioning
confidence: 99%
“…The proteases would degrade the protein phase, thus providing a conduit for their further infiltration into the mineral, which would increase the area of exposed crystal surface and thus facilitate crystal mineral dissolution in the acidic interior. In a previous study we demonstrated qualitatively that Madin-Darby canine kidney (MDCK-II) cells, which exhibit features of proximal/distal tubule cells (50), caused more extensive degradation of COM crystals generated from centrifuged and filtered urine, than those precipitated from the corresponding ultrafiltered (UF) urine (7). The aims of this investigation were 1) to measure the nonuniform strain and crystallite size of COM crystals precipitated from urine containing increasing amounts of the soluble crystal matrix extract (CME) derived from urinary COM crystals and 2) to compare quantitatively their rates of dissolution after attachment to renal epithelial cells.…”
mentioning
confidence: 99%
“…Consequently, crystals move from the tubular lumen to the interstitum of the kidney [9][10][11][18][19][20]. In this case, it was observed ultrastructurally that some crystal ghosts are extending from the tubular epithelium to the interstitium through the basement membrane, which suggests that similar transport of calcium oxalate crystals from the luminal surface to the peritubular interstitium might also occur in the present case.…”
mentioning
confidence: 54%